2021
DOI: 10.1002/cnr2.1374
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practice of cervical cancer screening among women living with HIV in the Kilimanjaro region, northern Tanzania

Abstract: Background: Cervical cancer is the fourth most common cancer globally among women in incidence and mortality. Women living with HIV (WLHIV) are disproportionately at a higher risk of developing the disease.Aim: To determine the knowledge, attitude, and practice of cervical cancer screening among WLHIV in the Kilimanjaro region, northern Tanzania, following the integration of these services in routine HIV care in the country. Methods and results:A cross-sectional study was conducted in the Kilimanjaro region am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…Kasa, et al [100] reported that out of 735 women recruited in their study to assess attitude and knowledge of cervical cancer in North West Ethiopia, only 7.3% of respondents had ever been screened for cervical cancer, while 172 (23.1%) were knowledgeable of the disease and 63% of the respondents had a negative attitude toward the disease. Similar studies in Tanzania, Kenya, Cameroun, Sudan and Ethiopia have reported a low level of awareness and knowledge of cervical cancer in women residing in these countries [121][122][123][124][125][126]. The time required by primary healthcare professionals in Lagos to detect and refer cervical cancer patients to a tertiary health facility for treatment and management was an essential factor in patients presenting with an advanced stage of the disease.…”
Section: Awareness and Knowledge Of Cervical Cancer In Africamentioning
confidence: 95%
“…Kasa, et al [100] reported that out of 735 women recruited in their study to assess attitude and knowledge of cervical cancer in North West Ethiopia, only 7.3% of respondents had ever been screened for cervical cancer, while 172 (23.1%) were knowledgeable of the disease and 63% of the respondents had a negative attitude toward the disease. Similar studies in Tanzania, Kenya, Cameroun, Sudan and Ethiopia have reported a low level of awareness and knowledge of cervical cancer in women residing in these countries [121][122][123][124][125][126]. The time required by primary healthcare professionals in Lagos to detect and refer cervical cancer patients to a tertiary health facility for treatment and management was an essential factor in patients presenting with an advanced stage of the disease.…”
Section: Awareness and Knowledge Of Cervical Cancer In Africamentioning
confidence: 95%
“…The methods applied in this study are also published elsewhere ( Kimondo et al, 2021 ). Briefly, we carried out a health facility-based cross-sectional study design in the Kilimanjaro region between August 21 and September 3, 2020.…”
Section: Methodsmentioning
confidence: 99%
“…In Tanzania, the prevalence ranges from 7.3 % in Mwanza to 11 % in Morogoro ( Kafuruki et al, 2013 , Chambuso et al, 2017 ). This high prevalence might be partly contributed to by poor cervical cancer screening among women ( Kimondo et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cervical cancer is the fourth leading cause of cancer-related death in women worldwide [1,2] . According to GLOBOCAN 2018 cancer statistics, there were estimated 569,847 new cases and 311,365 deaths from cervical cancer worldwide in 2018 [2] .…”
Section: Introductionmentioning
confidence: 99%